Unraveling Allostery in a Knotted Minimal Methyltransferase by NMR Spectroscopy. Issue 9 (17th April 2020) - Capraro, Dominique T.; Burban, David J.; Jennings, Patricia A.
Abstract: The methyltransferases that belong to the SpoU-TrmD family contain trefoil knots in their backbone fold. Recent structural dynamic and binding analyses of both free and bound homologs indicate that the knot within the polypeptide backbone plays a significant role in the biological activity of the molecule. The knot loops form the S -adenosyl-methionine (SAM)-binding pocket as well as participate in SAM binding and catalysis. Knots contain both at once a stable core as well as moving parts that modulate long-range motions. Here, we sought to understand allosteric effects modulated by the knotted topology. Uncovering the residues that contribute to these changes and the functional aspects of these protein motions are essential to understanding the interplay between the knot, activation of the methyltransferase, and the implications in RNA interactions. The question we sought to address is as follows: How does the knot, which constricts the backbone as well as forms the SAM-binding pocket with its three distinctive loops, affect the binding mechanism? Using a minimally tied trefoil protein as the framework for understanding the structure–function roles, we offer an unprecedented view of the conformational mechanics of the knot and its relationship to the activation of the ligand molecule. Focusing on the biophysical characterization of the knot region by NMR spectroscopy, we identify the SAM-binding region and observe changes in the dynamics of the loops that form the knot. Importantly, we also observe long-range allosteric changes in flanking helices consistent with winding/unwinding in helical propensity as the knot tightens to secure the SAM cofactor. Graphical abstract: Unlabelled Image Highlights: Native state dynamics reveals knot loops modulate allosteric changes Chemical shift analyses confirm knot loops form the binding pocket Knot loops bind, clamp and bend SAH, and propagate binding energy Binding induces conformational changes in loops and helices distal to the knot loops